Applying a Contest to Improve Learning in the Information Systems Development - An Interdisciplinary and Extracurricular Approach - Marcelo FANTINATO; Marcos Lordello CHAIM; Marcelo MORANDINI; Sarajane Marques PERES; Esteban Fernandez TUESTA (Informatics in Education, 2011)
Contests are usually applied in the academic environment to simulate real professional situations that require from the participants a more pro-active attitude than the one shown in conventional coursework. Although they are commonly applied in the scope of a unique course, the contest described here was an extracurricular experience applied in an Information System undergraduate program. The evaluation of the contest is also presented; the objective was to assess the role of the contest as a tool to bring together interdisciplinary subjects, complementary to the traditional disciplinary structure of the program curriculum. The results indicate that a significant portion of the participants noticed increase in their knowledge after the contest, which is verified by statistical tests. However, students from the first stages received more benefits, probably because such students were more motivated and had more available time to be involved in the contest activities.